"IMPROVING THE USE OF MODERN FINANCIAL TECHNOLOGIES IN THE BANKING SYSTEM" (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the digital economy, the introduction of modern financial technologies in banking activities significantly increases the competitiveness of banks. In this regard, digital banks have an accelerating effect on economic activity, allowing them to carry out financial transactions anytime and anywhere.